2009
DOI: 10.1111/j.1365-2869.2008.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

The relation between common sleep problems and emotional and behavioral problems among 2‐ and 3‐year‐olds in the context of known risk factors for psychopathology

Abstract: SUMMAR Y The contribution of sleep problems to emotional and behavioral problems among young children within the context of known risk factors for psychopathology was examined. Data on 2-and 3-year-olds, representative of Canadian children without a chronic illness, from three cross-sectional cohorts of the Canadian National Longitudinal Study of Child and Youth were analysed (n = 2996, 2822, and 3050). The person most knowledgeable (PMK), usually the mother, provided information about her child, herself, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 55 publications
2
76
1
4
Order By: Relevance
“…27,28 Sleep is independently related to emotional and behavioral problems and is not accounted for by shared risk factors among preschool children. 29 This association is further supported in school-aged children when extending sleep duration was associated with improved emotional regulation. 30,31 Sleep interventions in children with sleep problems have also shown positive effects on daytime functioning.…”
Section: Discussionmentioning
confidence: 87%
“…27,28 Sleep is independently related to emotional and behavioral problems and is not accounted for by shared risk factors among preschool children. 29 This association is further supported in school-aged children when extending sleep duration was associated with improved emotional regulation. 30,31 Sleep interventions in children with sleep problems have also shown positive effects on daytime functioning.…”
Section: Discussionmentioning
confidence: 87%
“…2,3 Compensation of sleep debt during weekends with .2 hours of discrepancy was often documented among young students. 4,5 Sleep deprivation is associated with daytime sleepiness, attention impairment, and poor academic performance, [6][7][8][9] and it is also empirically linked to heightened risk of mood disorders, obesity, hyperlipidemia, and high blood pressure in young students. [10][11][12][13][14] An interactive network of internal and external factors contributes to insufficient sleep in adolescents.…”
Section: What This Study Addsmentioning
confidence: 99%
“…In a Canadian longitudinal study of 2-to 3-year-olds (approximately 9,000 children during three waves of investigation), Reid, Hong, and Wade (2009) found that difficulties initiating or maintaining sleep-type problems were as strong a correlate of internalizing (i.e., anxiety) and externalizing (i.e., hyperactivity/aggression) problems as wellestablished risk factors, such as maternal depression. Among Australian 4-to 5-year-olds (n 5 4,983), the prevalence of mild and moderate/severe sleep problems was 14% and 20%, respectively, with an approximate doubling of effect size for quality of life and conduct outcomes, from no to mild and from mild to moderate/severe sleep problems.…”
Section: How Do Sleep Problems Affectmentioning
confidence: 99%